Quality of Leadership and Implicated Constructs - Seco, Victor Manuel Monteiro (2019)
Purpose: The authors examine the role of values, trust, organizational culture, learning organizations and authentic leadership in explaining the quality of leadership. Design/Methodology: This is a theoretical text that allows approaches and intersections of the constructs with implications for the quality of leadership. Contributions/Findings: This present literature review confirms that there is a significant connection between authentic leadership and its components according to different authors’ point of view. Research Limitations/Implications: It is necessary to consider further some other important authors’ positions that are not considered in the present review. It was made a focused author’s selection of different continents and realities. Originality/Value: This review contributes to enhance the compilation of existing research on the examination of authentic leadership and its most important components.